(Nano)microplastics promote the propagation of antibiotic resistance genes in landfill leachate. Issue 11 (8th October 2020) - Shi, Jianhong; Wu, Dong; Su, Yinglong; Xie, Bing
Abstract : Municipal landfill leachate is a huge reservoir of (nano)microplastics (N/MPs) and antibiotic resistance genes (ARGs). Abstract : Municipal landfill leachate is a huge reservoir of (nano)microplastics (N/MPs) and antibiotic resistance genes (ARGs). N/MPs have a proven ability to affect the growth of bacteria and composition of bacterial communities, which may further influence the spread of ARGs in the environment. To extrapolate the interactions between these two emerging contaminants, we investigated the variations of the ARG levels in leachate with exposures to different sizes of N/MPs. The results showed that ARGs were enriched in the N/MPs-exposed groups, especially in the 200–500 nm MP group. Notably, the enrichment became more pronounced in the long-term exposure samples than the short-term ones. Together with this process, the total abundance of bacteria, as well as the potential ARG-carrying bacteria, also increased in the N/MP-exposed groups, and the long-term N/MP exposure led more bacteria genera, such as Pseudomonas, Syntrophomonas, and Desulfotomaculum, to become closely associated with ARG variations. Meanwhile, the production of reactive oxygen species (ROS) induced by exposure to the 50–100 nm NPs and the 200–500 nm MPs was observed to increase bacterial membrane permeability, which might result in more bacteria becoming potential receptors of ARGs via the intra-bacterial community transfer of mobile genetic elements. Overall, the current study demonstrated that the presence of N/MPs in leachate promoted the propagation of ARGs due to their impacts on the bacterial community and cellular membrane permeability. These findings have important implications for understanding the environmental risks of the combined pollution of N/MPs and ARGs.